From Directive to Facilitative: Interactional Strategies Influencing Student Participation in Online ELT Classroom - Fella Rosy; Didin Nuruddin Hidayat; Nida Husna; Shirley Baker (Universitas Cokroaminoto Palopo, 2026)
This study investigates the effects of various teaching strategies on student engagement in an English Language Teaching (ELT) classroom at the university level. Data from a 90-minute online postgraduate course on second language acquisition were gathered using qualitative discourse analysis, through recorded classroom interaction conducted via Zoom. For identifying collaborative, directive, probing, scaffolding, and facilitative interactional strategies, this study used qualitative discourse analysis of a 90-minute online postgraduate class on second language acquisition. Five illustrative examples of interaction were chosen from an online class conducted on Zoom, and discourse analysis was carried out using these examples to identify teacher discourse strategies and their impact on student participation. Autonomy and multidirectional communication were further encouraged via collaborative interactions. Conversely, directive methods resulted in fewer replies and lower levels of participation. Discourse evidence indicates that collaborative and facilitative techniques fostered more extended learner responses and sustained engagement, whereas directive moves discouraged engagement. this study makes a contribution with empirical findings from an EFL context in an Indonesian university setting in providing evidence that student-centered and interactionally responsive approaches to teaching, in particular when using facilitative questioning, scaffolding, probing, and collaborative discourse, have a major positive impact on online English class participation and meaning-making, in contrast to directive teaching approaches which have a constraining effect on online interaction.